EFEKTIFITAS LATIHAN WALLPASS TERHADAP KETEPATAN PASSING DALAM SEPAK BOLA ATLET U12 SSB TALENTA ACEH FOOTBALL ACADEMY - Is, Zulheri; Hariansyah, Septi; irwandi, irwandi (Sport Pedagogy Journal, 2023)
Football is a team game in which two teams compete against each other involving physical, technical, tactical, and mental elements. This study aims to examine the influence of wallpass training on the accuracy of passing in extracurricular football activities for athletes of SSB Talenta Aceh Football Academy. This study uses an experimental method with a one group pretest posttest design. The sample in this study consists of 18 students who participate in extracurricular football activities.The research results show that there is an average for the pretest score of 6.05 and the posttest score of 7.83. The median middle value for the pretest score is 6 and the posttest score is 7. The mode for the pretest score is 6 and the posttest score is 8. The standard deviation for the pretest score is 0.801 and the posttest score is 0.708. Based on the results of the normality test data in the table above, it shows that the pretest has a result of 0.062 and the posttest has a result of 0.040, so it can be interpreted that the research data is normally distributed.The average results of the pre-test and post-test or to determine whether there is a significant effect on wallpass training. From the t-test results, it can be seen that the t-value is 3.738 and the t-table is 2.131, indicating a significant difference between the pre-test and post-test. Therefore, the alternative hypothesis Ha stating that there is a significant effect of wallpass training on passing accuracy is used as a training to improve passing accuracy